Biosensor‐Enabled Directed Evolution to Improve Muconic Acid Production in Saccharomyces cerevisiae. Issue 10 (24th August 2017) - Leavitt, John M.; Wagner, James M.; Tu, Cuong C.; Tong, Alice; Liu, Yanyi; Alper, Hal S.
Abstract : Muconic acid is a valuable platform chemical with potential applications in the production of polymers such as nylon and polyethylene terephthalate (PET). The conjugate base, muconate, has been previously biosynthesized in the bacterial host Escherichia coli . Likewise, previous significant pathway engineering lead to the first reported instance of rationally engineered production of muconic acid in the yeast Saccharomyces cerevisiae . To further increase muconic acid production in this host, a combined adaptive laboratory evolution (ALE) strategy and rational metabolic engineering is employed. To this end, a biosensor module that responds to the endogenous aromatic amino acid (AAA) as a surrogate for pathway flux is adapted. Following two rounds of ALE coupled with an anti‐metabolite feeding strategy, the strains with improved AAA pathway flux is isolated. Next, it is demonstrated that this increased flux can be redirected into the composite muconic acid pathway with a threefold increase in the total titer of the composite pathway compared to our previously engineered strain. Finally, a truncation of the penta‐functional ARO1 protein is complemented and overexpress an endogenous aromatic decarboxylase to establish a final strain capable of producing 0.5 g L −1 muconic acid in shake flasks and 2.1 g L −1 in a fed‐batch bioreactor with a yield of 12.9 mg muconic acid/g glucose at the rate of 9.0 mg h −1 . This value represents the highest titer of muconic acid reported to date in S. cerevisiae, in addition to the highest reported titer of a shikimate pathway derivative in this host. Abstract : To improve the muconic acid production in Saccharomyces cerevisiae, an adaptive laboratory evolution strategy is employed by adapting a biosensor module which responds to the endogenous aromatic amino acid as a surrogate for pathway flux. After two rounds of evolution followed by pathway optimization, a final strain capable of producing the highest titer of muconic acid reported to date in S. cerevisiae is established, in addition to the highest reported titer of a shikimate pathway derivative in this host.